PENGARUH KOMUNIKASI INTERPERSONAL DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN KORESPONDENSI SISWA KELAS X SMK NEGERI 1 KABANJAHE - Tauada Silalahi; Nelly Armayanti; Rani Lestary Br Sitepu (Smart Education, 2026)
This study aimed to determine the influence of interpersonal communication and learning motivation on the learning achievement of tenth-grade students in the Correspondence subject at SMK Negeri 1 Kabanjahe. This research employed a quantitative approach with a population of 108 students and a sample of 85 students. Data were collected through questionnaires and documentation and analyzed using multiple linear regression. The results showed the regression equation Y = 62.040 + 0.078X₁ + 0.261X₂. Partially, interpersonal communication had no significant effect on learning achievement (t = 0.972; p = 0.334), whereas learning motivation had a positive and significant effect (t = 4.817; p < 0.001). Simultaneously, both variables significantly affected learning achievement (F = 58.234; p < 0.001). The coefficient of determination indicated that the model explained 57.7% of the variance in learning achievement. Learning motivation was the dominant factor affecting students' learning achievement.